Influence of dietary fat intake on the endocannabinoid system in lean and obese subjects. (11th March 2014) - Engeli, Stefan; Lehmann, Anne‐Christin; Kaminski, Jana; Haas, Verena; Janke, Jürgen; Zoerner, Alexander A.; Luft, Friedrich C.; Tsikas, Dimitrios; Jordan, Jens
<x xml:space="preserve">Abstract</x> Objective Endocannabinoid system (ECS) activation promotes obesity‐associated metabolic disease. Increased dietary fat intake increases blood endocannabinoids and alters adipose and skeletal muscle ECS gene expression in human. Methods Two weeks isocaloric low‐ (LFD) and high‐fat diets (HFD) in obese (n = 12) and normal‐weight (n = 17) subjects in a randomized cross‐over study were compared. Blood endocannabinoids were measured in the fasting condition and after food intake using mass spectrometry. Adipose and skeletal muscle gene expression was determined using real‐time RT‐PCR. Results Baseline fasting plasma endocannabinoids were similar with both diets. Anandamide decreased similarly with high‐ or low‐fat test meals in both groups. Baseline arachidonoylglycerol plasma concentrations were similar between groups and diets, and unresponsive to eating. In subcutaneous adipose tissue, DAGL‐α mRNA was upregulated and fatty acid amide hydrolase (FAAH) and monoacylglycerol lipase (MAGL) mRNAs were down‐regulated in obese subjects, but the diets had no influence. In contrast, the HFD produced pronounced reductions in skeletal muscle CB1‐R and MAGL mRNA expression, whereas obesity did not affect muscular gene expression. Conclusions Weight‐neutral changes in dietary fat intake cannot explain excessive endocannabinoid availability in human obesity. Obesity and dietary fat intake affect ECS gene expression in a tissue‐specific manner.